IMPLEMENTASI SERVER CLOUD STORAGE MENGGUNAKAN SFTPGO, DOCKER, DAN CLOUDFLARE TUNNEL - Bahalwan, Zen Aufa; Febriawan, Dimas (Jurnal Teknik Informatika dan Komputer, 2025)
The implementation of a cloud storage server based on SFTPGo allows users to access and manage file storage via WebGUI and SFTP clients. This study aims to develop a secure and easily accessible cloud storage system using Docker and Cloudflare Tunnel technology. The system is implemented on a Linux-based server and tested in various scenarios to ensure the reliability of WebGUI access and connectivity via the SFTP protocol. The implementation results show that the combination of SFTPGo, Docker, and Cloudflare Tunnel provides a flexible and secure storage environment. With this mechanism, users can upload and download files using predefined credentials, while ensuring that SFTP access is only possible through Cloudflare Tunnel, enhancing system security.